Chemostratigraphy of Late Sinemurian – Early Pliensbachian shallow-to deep-water deposits of the Central High Atlas Basin: Paleoenvironmental implications. (May 2019) - Danisch, Jan; Kabiri, Lahcen; Nutz, Alexis; Bodin, Stéphane
Abstract: Shallow water carbonate rocks are especially prone to diagenetic alteration. As such they are sometimes problematic archives of past carbon cycle perturbations, casting doubt on the reliability of shallow-water carbonates carbon isotopes analyses for chemostratigraphic purposes. In this paper, bulk organic carbon isotopes (δ 13 Corg ) is used as a robust replacement of the more sensitive carbonate carbon isotope systems for the establishment of a refined chronostatigraphic framework for the evolution of Sinemurian-Pliensbachian neritic carbonate systems in the Central High Atlas Basin of Morocco. These data show very similar patterns and characteristics in the organic carbon isotope curves of basinal and platform sections and thus illustrate the reliability of these archives. Simultaneously, we explore the expression of the global carbon isotope excursion at the Sinemurian-Pliensbachian boundary (SP event) in the study area in Morocco. This event has been previously described as a negative carbon isotope excursion of ∼2‰ associated with a large transgression in numerous basins. In Morocco and other neritic carbonate records, the SP event is better described as a return to previous values after a positive carbon isotope excursion coinciding with a major latest Sinemurian regression recognised on a global scale. Similar patterns are also found in other sections, although sometimes poorly expressed. However, it shows, that the SP event has ambiguous characteristics and questions the conventional hypothesis of it being linked to the massive injection of 13 C-depleted carbon into the atmosphere-ocean system. Highlights: Carbon isotope chemostratigraphic constrain on Sinemurian-Pliensbachian sections. A positive C-isotope excursion characterizes the latest Sinemurian. The SP event is a return to background C-isotopes values.